2003
DOI: 10.2355/isijinternational.43.348
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phosphorus on Solidification Structure in Continuously Cast 0.1 mass% Carbon Steel.

Abstract: In 0.1 mass% carbon steels with phosphorus contents ranging from 0.01 to 0.2 mass%, slabs were continuously cast to a thickness of 100 mm with a laboratory scale caster. Their macro-and micro-structures were characterized, focusing on the effects of phosphorus addition on the structural evolution during solidification and subsequent cooling. Cast slabs of high phosphorus steels have a fine columnar-g-grain structure. The mean width of the columnar grain was approximately half of that in the cast slabs without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
1
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 22 publications
0
59
1
5
Order By: Relevance
“…Figure 12 shows the prediction of the growth rate of the interface between the austenite and ferrite in holding at given temperatures for the 0.4 and 0.8 % Mn compositions. 16) The present prediction says that although the difference is not large, a lower growth rate is expected for the 0.8 % Mn than for the 0.4 % Mn. When we assume that the transformation starts after the compression below 1 093 K and finishes above 973 K, the ferrite size may reach a value between 2 and 5 mm in 3 s. The lower the transformation temperature range, the more the growth.…”
Section: Influence Of Mn Segregation On Nucleation Andmentioning
confidence: 80%
See 2 more Smart Citations
“…Figure 12 shows the prediction of the growth rate of the interface between the austenite and ferrite in holding at given temperatures for the 0.4 and 0.8 % Mn compositions. 16) The present prediction says that although the difference is not large, a lower growth rate is expected for the 0.8 % Mn than for the 0.4 % Mn. When we assume that the transformation starts after the compression below 1 093 K and finishes above 973 K, the ferrite size may reach a value between 2 and 5 mm in 3 s. The lower the transformation temperature range, the more the growth.…”
Section: Influence Of Mn Segregation On Nucleation Andmentioning
confidence: 80%
“…A continuous cast slab made in a laboratory-scale was prepared for the present study. The details of the casting are reported in the literature by Yoshida et al 16) and also mentioned in Table 3 with other preparations for GRP samples. The average spacing of the primary dendrite arms was 318 mm and the average spacing of the secondary dendrite arms was 137 mm.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16) Moreover, it was reported that P addition led to the refinement of as-cast g grain structure in 0.1 mass% C steel. [8][9][10] It was discussed that the increase in P concentration significantly lowers T g and P segregation developed during casting process provides the pinning effect. In our previous study, we investigated the effects of Al addition on the as-cast g grain structure in 0.2 mass% C steel.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] The addition of d-ferrite stabilizing elements such as Nb, V and Mo extends the dϩg region in the phase diagram toward lower temperatures, which leads to refinement of as-cast g grain structure due to pinning effect of the d phase on the g grains. 15,16) Moreover, it was reported that P addition led to the refinement of as-cast g grain structure in 0.1 mass% C steel.…”
Section: Introductionmentioning
confidence: 99%